O05.4 Association Between Chlamydia Trachomatis Genital Infection and the Vaginal Microbiome. (13th July 2013) - Ma, B; Brotman, R M; Gajer, P; Fadrosh, D; Mahurkar, A; White, O; Terplan, M; Bavoil, P; Forney, L J; Ravel, J
Abstract : Background: Chlamydia trachomatis (CT) genital infection is one of the most widespread sexually transmitted infections (STIs). It is thought that certain types of vaginal microbiota are better able to prevent STIs, however, very little is known about the relationships between species and genomic composition of the vaginal microbiome and risk of infection. Information about these can be used to advance prevention strategies for STIs. We sought to characterise the vaginal microbiome at the time of diagnosis and after treatment of CT infection. Methods: 101 women with CT genital infection were recruited to a longitudinal study in Baltimore, MD. Participants were treated at diagnosis and returned for clinical visits every 3 months for 9 months, at which times the vaginal microbiota was determined using 16S rRNA analysis. We further applied high-throughput metagenomics to characterise the genomic makeup of the vaginal microbiome. Results: The average age of participants was 19.3 (range 14–28) and 92% were African-American. During CT infection, comprehensive surveys of the vaginal microbiota demonstrated two distinct community state types characterised by: (1) a complex assemblage of strict anaerobes with low proportions of Lactobacillus spp. (60% of samples) or (2) a high relative abundance of Lactobacillus iners- dominated communities (37% of samples) . Metagenomic evaluation suggested unique characteristics of the genomes of the dominant species in these communities (i.e., L. iners, Gardnerella vaginalis ). L. iners appeared more genetically diverse than other Lactobacillus species. Conclusions: Complex communities of strict anaerobes with low proportions of Lactobacillus or specific L. iners genome types represented a hallmark of the chlamydia - infected state in this population. Some L. iners may be better suited to adapt to diverse environments while others may be contributing factors to an at-risk microbiome. In the era of personalised medicine, future work will enhance our ability to intervene and establish a protective vaginal microbiome.